Planejamento de carreira e realização profissional dos docentes de ciências contábeis - Araújo, Tamires Sousa (2018)
Career definitions have changed over time. The professional who felt these changes was the teacher, who today is the center of attention in the educational environment and, consequently, planner of your own career, which is considered an important factor for success in working life. The purpose of this study was to analyze whether self-efficacy influences the planning of the career choice in the accounting area and how much planning affects the teachers’ professional achievement. For this purpose, three components were used: the Social Cognitive Career Theory (SCCT), created by Lent, Brown and Hackett (2002), whose objective is to identify, through self-efficacy, previous experiences and personal factors that can explain how individuals form career interests, set goals, and persist in the work environment. For career planning, the theoretical basis 'career decision' by Lounsbury et al. (2005) and 'vocational exploration' by Rogers, Creed and Glendon's (2008) were used with the purpose of identifying career planning for teachers. Finally, the scale of professional achievement (ERP) developed by Oliveira-Silva (2015), which determines how much individuals are professionally accomplished, was used to measure professional achievement. The data collection instrument was adapted from Teixeira (2010) and Oliveira-Silva (2015) and was stored in an online platform from November 19, 2017 to February 2, 2018. The research is classified as descriptive and the quantitative approach was used for data analysis. In addition, confirmatory factor analysis and structural equation modeling (SEM) were used to test the proposed model in the thesis. The sample consisted of 542 teachers from the Accounting Sciences course of federal and state higher education institutions, of which 57.4% are male, aged between 30 and 49 years (58.9%). Most of the professors are concentrated in the South and Southeast regions (62.2%), of which 84.3% have Accounting Sciences education and 82.6% have stricto sensu education (Master's or PhD). Regarding the teaching experience, it was possible to note that 68.7% of the sample have between 7 and 25 years of teaching experience, of which 85.1% are teachers of an effective regime. When analyzing the relationship between the constructs of self-efficacy, career planning (career exploration) in professional achievement, the results presented evidence that this relationship explains the model in 61%. Moreover, the hypothesis tests showed that self-efficacy positively affects the teaching career planning and that the planning of the choice of the teaching career in the accounting area affects the perception of professional achievement. It is understood that the results of this thesis can add to the literature the refinement of the constructs that deal with self-efficacy, career planning and professional achievement.